Techno-economic assessment for a pumped thermal energy storage integrated with open cycle gas turbine and chemical looping technology. (1st March 2022) - Bahzad, Husain; Fennell, Paul; Shah, Nilay; Hallett, Jason; Ali, Naser
Highlights: The roundtrip efficiency for both systems developed was 77%. The integrated pumped thermal energy system showed a better economic performance. The operating scenarios affects systems feasibility. The gas turbine based system is more feasible at hydrogen feed% above 37% for day1 . Errors in fuel cost significantly impacts the daily profits by ± 43% at ± 25% error. Abstract: Pumped thermal energy storage offers a high energy density, potentially resulting in a relatively low cost per unit of energy stored. In this study, two novel energy storage systems were developed. The first system was developed by integrating pumped thermal energy storage and chemical looping technologies, whereas the second was formed by merging the first system with an open cycle gas turbine. Both systems used an oxygen depleted stream as a working fluid and iron-based oxygen carriers from a chemical looping water splitting process storage material for the pumped thermal energy storage system. In addition, hydrogen from the chemical looping process was employed for the gas turbine in the second system. Both systems were evaluated thermodynamically via the determination of the roundtrip efficiency. The results presented here indicate that the roundtrip efficiency of both systems developed was 77%. Furthermore, the capital requirements, operating costs, and daily profits from electricity generation were calculated for both systems over several days within the year. The capital and operating costs for the several days that were simulated for the integrated pumped thermal energy storage system were lower than that of a gas turbine based system. Consequently, the daily profit was estimated and found to be between 4.9% and 72.9% higher for the integrated pumped storage relative to the gas turbine based system. Moreover, an economic sensitivity analysis was performed to identify the factors that strongly affect the daily profits of the gas turbine system relative to the pumped storage system. Based on the analysis, the optimal hydrogen fuel percentage fed to the open cycle gas turbine was calculated for the days simulated. Finally, the impact of % error on the estimated capital and fuel production costs on daily profits were investigated. The outcome revealed a higher impact of computational errors on the fuel costs relative to the costs of the capital.